Femtosecond laser photochemical reduction of silver ion solution for micro-welding of transparent and hard materials for solar cell packaging - Hao Chen; Zhaoxu Li; Mingyang Han; Xiao Yang; Zhimin Liang; Shi Bai (Materials & Design)
Transparent and hard materials are extensively employed in the fabrication of integrated devices. Ultrafast laser micro-welding technology serves as an efficient method for joining such materials. However, initiating multiphoton absorption in transparent materials necessitates high pulse energy, and a polished surface forming optical contact is crucial for ensuring reliable laser welding. Consequently, achieving high-quality connections of transparent materials under non-optical contact conditions presents a challenge. In this study, a silver ion solution was utilized as an intermediate layer for femtosecond laser micro-welding of glass and heterogeneous materials. The findings demonstrated that photochemically reduced silver nanoclusters increased the shear strength of glass to 27.36 MPa at a low input energy density (2.4J/cm2). Furthermore, the quality of the connection and sealing reliability were assessed through thermal shock and waterproof evaluations. The results indicated that femtosecond laser welding assisted by a silver ion solution is an effective and energy-efficient technique for achieving high-quality connections of non-optically contacted transparent materials, offering a promising approach for applications such as solar cell packaging.